Head anatomy of a lantern shark wet‐collection specimen (Chondrichthyes: Etmopteridae). Issue 5 (25th January 2023) - Staggl, Manuel Andreas; Ruthensteiner, Bernhard; Straube, Nicolas
Abstract: In this study, we apply a two‐step (untreated and soft tissue stained) diffusible iodine‐based contrast‐enhanced micro‐computed tomography array to a wet‐collection Lantern Shark specimen of Etmopterus lucifer . The focus of our scanning approach is the head anatomy. The unstained CT data allow the imaging of mineralized (skeletal) tissue, while results for soft tissue were achieved after staining for 120 h in a 1% ethanolic iodine solution. Three‐dimensional visualization after the segmentation of hard as well as soft tissue reveals new details of tissue organization and allows us to draw conclusions on the significance of organs in their function. Outstanding are the ampullae of Lorenzini for electroreception, which appear as the dominant sense along with the olfactory system. Corresponding brain areas of these sensory organs are significantly enlarged as well and likely reflect adaptations to the lantern sharks' deep‐sea habitat. While electroreception supports the capture of living prey, the enlarged olfactory system can guide the scavenging of these opportunistic feeders. Compared to other approaches based on the manual dissection of similar species, CT scanning is superior in some but not all aspects. For example, fenestrae of the cranial nerves within the chondrocranium cannot be identified reflecting the limitations of the method, however, CT scanning is less invasive, and the staining is mostly reversible and can be rinsed out. Abstract : In this study, we present a two‐step micro‐computed tomography array to a 39‐year‐old wet‐collection Lantern Shark specimen of Etmopterus lucifer . The focus of our scanning approach is the head anatomy showing numerous internal structures, for example the ampullae of Lorenzini, the olfactory system and major brain areas. Significantly enlarged sensory systems likely reflect adaptations to the lantern sharks' deep‐sea habitat.